The critical path : - Yates, Brock (Little, Brown, 1996)
After a series of unsatisfactory models that pushed the company to the brink of extinction, the Chrysler Corporation did a revolutionary thing: It listened to its customers. What they told the company was that they wanted a family vehicle that didn't drive like an 18-wheeler. Chrysler responded with its minivans, introducing a new category of vehicles to the American public and resuscitating its floundering finances. Brock Yates, a columnist for Car & Driver magazine, reconstructs this tale with a mix of knowledge about vehicle engineering, the automobile industry, and the American public. A must-read for those in the industry and others interested in corporate survival.